Tergerusnya Bahasa Indonesia oleh Bahasa Asing Studi Kasus Penggunaan Bahasa pada Papan Iklan di Kota Singkawang - NFN Martina; NFN Harianto (Balai Bahasa Kalimantan Barat, 2016)
A wise man said that the language showed his nation identity. The nation dignified is they have a pride of using their own language. This expression is very urgent in view of the application raised public use of language is very worrying. This concern is justified because the results of the research team of West Kalimantan Provincial Language Institute in 2015 on the use of language in the public space outside Singkawang showed indifference writer in applying the correct language (mixed language). Erosion of language use outside the public sphere, indicating that the language does not have enough awareness and knowledge of the ideas of creativity in the language. Problems in this paper is the erosion of Indonesian by a foreign language on billboards in Singkawang. This paper describes the erosion of Indonesian by a foreign language on billboards in Singkawang. Descriptive method used in describing the findings in the field of data in this writing. The analysis showed that the erosion of the use of Indonesian by a foreign language, especially on billboards in Singkawang. The use of foreign languages is dominated by English and Chinese (Khek). Foreign language form of intervention in the form of code-mixing, code switching, and use a foreign language pure.